Measurement of field-free alignment of jet-cooled molecules by nonresonant femtosecond degenerate four-wave mixing - Ren, Xiaoming; Makhija, Varun; Kumarappan, Vinod (My University, 2012)
A femtosecond degenerate four-wave mixing (fs-DFWM) technique for probing the alignment of molecules is described. The rotational wave packet generated by a strong pump beam modulates the nonresonant third-order susceptibility of the gas and this modulation is observed using a noncollinear background-free setup. As a demonstration of the technique, we measure the alignment of a linear molecule (nitrogen), a symmetric top (benzene), and an asymmetric top (iodobenzene) in a supersonic jet. The measured signal is shown to agree well with calculations of the nonresonant third-order susceptibility from the solution of the time-dependent Schrödinger equation. The pump-DFWM measurement scheme can be used with dilute jet-cooled targets, allows arbitrary pump pulses to be used, and is rapid enough to be incorporated into a feedback optimization loop. The scheme can easily be made polarization-sensitive, indicating the possibility of measuring and optimizing three-dimensional alignment of asymmetric-top molecules.